The role of free radicals and nitric oxide in the ischemia-reperfusion injury mediated by acute bladder outlet obstruction - HAKLAR, GONCAGÜL; TARCAN, TUFAN (SPRINGER, 2008)
Free-radical generation and nitric oxide (NO) generation were detected in the rat bladder following acute bladder outlet obstruction (BOO), and the results were compared with those for vascular ischemia and reperfusion (I-R). Forty male Sprague Dawley rats were used. In the acute BOO plus I-R group (group 1), rats were catheterized with a 3-Fr catheter and an inflated balloon was positioned at the bladder neck. The bladder was overdistended after administration of Ringer solution and furosemide (12 mg/kg, each) for 60 min, and was then drained to allow reperfusion for 30 min. In the acute BOO plus nerve stimulation group (group 2), the pelvic nerve was stimulated in the distended bladder for 60 min (5 s every 5 min, 10 V/0.1 ms, 20 Hz). Pelvic nerve stimulation was performed in nonobstructed animals in group 3. In the I-R group (group 4), the distal aorta was occluded for 60 min followed by reperfusion for 30 min. Sham-operated animals served as the control group (group 5). At the end of the protocols, the levels of hydroxyl and superoxide radicals and NO levels were measured in the bladder tissues with luminol- and lucigenin-enhanced chemiluminescence methods. The results were compared by a one-way analysis of variance test. The levels of hydroxyl radicals were not significantly different between the study groups. In contrast, superoxide radicals and NO levels were significantly increased in both group 1 and group 4 compared with those in control animals (P < 0.05 for all comparisons). Superoxide radical generation in group 2 was comparable to the levels in group 1 (P > 0.05), whereas NO levels were substantially lower than in group 1 (P = 0.06). In summary, vascular I-R causes significant oxidative damage to the bladder. Acute BOO with overdistension of the bladder mimics the effects of true vascular I-R injury. The NO pathway has possibly a major role in I-R-induced bladder damage. Prolonged BOO may therefore significantly enhance the oxidative damage to the bladder and further accentuate the effects of generalized atherosclerotic processes in the elderly adult.
Keywords: experimental animal models; bladder outlet obstruction; ischemia-reperfusion injury; bladder; aging; RAT URINARY-BLADDER; RABBIT BLADDER; BLOOD-FLOW; CONTRACTION; RESPONSES; PROTECTS